Economic issues of food safety - Saidova Gulnoza Tulkunovna, (THE INNOVATION ECONOMY, 2026)
The article discusses the economic issues of ensuring food security, food safety, measures taken to develop the food industry, attract investment funds to the sector, and support export activities.